Push-out Evaluation on Metal and Fiber Posts Using Two Different Types of Cement in a Hyper-Narrow Environment - Shafigh, Elanz; Fekrazad, Reza; Bahrani, Mohammad Mehdi (European Journal of General Dentistry, 2022)
Objective Some teeth will be damaged due to caries, trauma, or previous improvement; posts are used to repair them. Underwater divers suffer from barodontalgia as a result of the tremendous amount of pressure they feel when diving. Meanwhile, barodontalgia instances involve teeth with defective restorations. Therefore, this study aimed to determine the push-out bond strength on metal and fiber posts using two different types of cement in a hyper-narrow environment.Materials and methods In this study, 96 single-rooted teeth, including central and lateral maxillary teeth and mandibular premolars were provided and underwent endodontic treatment. Root canal treatment, including cleaning the root canal using the manual and rotary files was performed in f2 size with 6% tipper. For purification, washing was performed in two steps with 5.25% sodium hypochlorite and normal saline, respectively. The obtained data were evaluated using statistical methods such as one-way analysis of variance and the Levene and Tamhane additional tests.Results The quantity of push-out strength was dramatically reduced in the metal posts and fibers groups due to increasing ambient pressure. The highest decrease rate was observed in the group of metal posts and resin cement. The highest bond strength in a typical environment was related to fiber posts, and among the fiber groups, those that had the highest bond strength were used as a combination of resin cement and fiber posts.Conclusion The highest level of bond strength among the study groups, at standard pressure and in a hyper-narrow environment, was related to fiber posts and resin cement. Therefore, the best choice for treatments for divers in a hyper-narrow climate is a combination of fiber posts and resin cement.
Keywords: barotrauma; barodontology; ambient pressure; bond strength